E-BOOKS - Kručena, Amalda Margita; Bēriņa, Gundega (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
The work describes the protection of e-books and their history, as well as the publishing house of electronic scientific books and magazines of the Rezekne Academy of Technology in the e-environment. This paper looks at general information about e-books and how it affects the operation and development of electronic publishing.